The Australian Desert Fireball Network: A new era for planetary science - Bland, Phil; Spurný, P.; Bevan, A.; Howard, K.; Towner, Martin; Benedix, Gretchen; Greenwood, R.; Shrbený, L.; Franchi, I.; Deacon, G.; Borovicka, J.; Ceplecha, Z.; et al. (Taylor & Francis Co Ltd, 2012)
Through an international collaboration between Imperial College London, the Ondrejov Observatory in the Czech Republic and the Western Australian Museum, the installation of the Australian Desert Fireball Network in the Nullarbor Region of Western Australia was completed in 2007. Currently, the Network, which is the first to be established in the southern hemisphere, comprises four all-sky autonomous observatories providing precise triangulation of fireball records to constrain pre-atmospheric orbits and fall positions of meteorites over an area of approximately 200 000 km2. To date, the Network has led to the successful recovery of two observed meteorite falls. The first recovery was three fragments (174, 150 and 14.9 g) of the same meteorite fall recorded on 20 July 2007 at 19 h 13 m 53.2 s±0.1 s UT that were found within 100 m of the predicted fall line. Named Bunburra Rockhole, the meteorite is a basaltic achondrite with an oxygen isotopic composition (Δ 17O = -0.112 %) distinguishing it from basaltic meteorites belonging to the Howardite–Eucrite–Diogenite clan thought to be derived from asteroid 4Vesta, and therefore must have come from another differentiated asteroid in the terrestrial planet region. Bunburra Rockhole was delivered to Earth from an Aten-like orbit that was almost entirely contained within the Earth’s orbit. The second recovered fall was detected by the Network on 13 April 2010 and led to the recovery of a 24.54 g meteorite fragment that is yet to be fully described. To date, the Network has recorded ~550 fireballs. Records from which precise orbits and trajectories can be determined number ~150. In addition to the two recovered falls twelve fireballs are considered to have resulted in meteorite falls. Of these, four are probable falls (10’s–100 g), and five are certain falls (>100 g). Having proved the potential of the Network, ultimately a large dataset of meteorites with orbits will provide the spatial context for the interpretation of meteorite composition that is currently lacking in planetary science.